2020
DOI: 10.18632/aging.103038
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation inhibits Val-boroPro-induced pyroptosis in THP-1 macrophages via sirtuin3 activation to promote autophagy and inhibit ROS generation

Abstract: INTRODUCTION Atherosclerosis (AS), a chronic inflammatory disease of the arterial wall characterized by gradual build-up of arterial plaque, is the main cause of cardiovascular disease (CVD) [1, 2]. Aging is a major, independent risk factor for AS [3]. Macrophages are main components of the inflammatory plaque and promote AS development across its different stages [4-6]. Accumulating data indicates that pyroptosis, a highly inflammatory form of programmed cell death usually triggered in immune cells upon infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 61 publications
0
35
0
Order By: Relevance
“…Furthermore, SIRT3 was shown to counteract pyroptosis by promoting autophagy and inhibiting the generation of ROS [ 92 ]. In this study, treatment with Dex suppressed activation of the NLRP3 inflammasome evidenced by the low expression levels of NLRP3, cleaved-caspase-1, ASC, and GSDMD consistent with the NLRP3 immunohistochemical staining results.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SIRT3 was shown to counteract pyroptosis by promoting autophagy and inhibiting the generation of ROS [ 92 ]. In this study, treatment with Dex suppressed activation of the NLRP3 inflammasome evidenced by the low expression levels of NLRP3, cleaved-caspase-1, ASC, and GSDMD consistent with the NLRP3 immunohistochemical staining results.…”
Section: Discussionmentioning
confidence: 99%
“…First, miR-103 targets BNIP3 (Bcl2/Adenovirus EIB 19 kDa Interacting Protein 3) to mediate late autophagy and relieve H 2 O 2 -induced oxidative stress and pyroptosis ( Wang et al, 2020 ). Second, electrical stimulation affects THP-1 macrophages, activates Sirt3, promotes autophagy, and relieves ROS-induced pyroptosis ( Cong et al, 2020 ). Third, adrenomedullin promotes autophagy and inhibits pyroptosis in testicular stromal cells through the ROS-AMPK-mTOR pathway ( Li et al, 2019 ).…”
Section: Autophagy Is a Double-edged Sword In Oamentioning
confidence: 99%
“…The relationships and interactions among in ammation, pyroptosis, ROS and autophagy have been widely studied. For example, Cong et al reported that electrical stimulation inhibited pyroptosis in THP-1 macrophages via sirtuin3 activation to promote autophagy and inhibit ROS generation 64 . Recent evidence revealed that lesions of the injured spinal cord led to mitochondrial damage, which contributed to the accumulation of ROS 65 .…”
Section: Discussionmentioning
confidence: 99%